How to pay for the debt — Coping with the Third World's crisis - Paul-Günther Schmidt (Intereconomics, 1990)
The Brady Plan is the first official proposal to give priority to a tangible reduction in the debtor countries' debt service burden and is thus a milestone along the path towards overcoming the international debt crisis. However, the instruments foreseen in the Plan virtually invite criticism and scepticism. What are the main inadequacies of the Brady Plan? How can the international debt strategy be developed further and made more effective?
Keywords: 330; Indebtedness